USE OF DIFFERENT ANTHROPOMETRIC TOOLS IN GENDER ANALYSIS OF MALNUTRITION IN DIVISION BAHAWALPUR - Muhammad Babar Alam; Rubeena Zakar; Muhammad Zeeshan Haroon (Journal of Ayub Medical College Abbottabad, 2023)
Previous studies highlighted that CIAF is better tool for malnutrition assessment which screen more children compared to other anthropometric approaches like MUAC, BMI for age, conventional indices (Stunting, Wasting and Underweight). In literature, none of the study has mentioned CIAF performance by gender in comparison with other anthropometric approaches. The study solves this puzzle, whether CIAF has the same performance in gender analysis too or not. Data from 1152 homes gathered using purposive random sample approach. The CIAF detects more malnourished children (63%) compared to other methods. Results show that male children in the study region had a greater frequency of malnutrition than female children. The results of the chi-square showed thatage and gender of the child have a significant relationship with CIAF than other approaches.The CIAF is a superior instrument for assessing child malnutritional status since it detects more malnourishedchildren even with gender analysis too.